2016
DOI: 10.1177/0271678x16638103
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a truly “iso-metabolic” gas challenge in physiological MRI

Abstract: Hypercapnia challenge (e.g. inhalation of CO 2 ) has been used in calibrated fMRI as well as in the mapping of vascular reactivity in cerebrovascular diseases. An important assumption underlying these measurements is that CO 2 is a pure vascular challenge but does not alter neural activity. However, recent reports have suggested that CO 2 inhalation may suppress neural activity and brain metabolic rate. Therefore, the goal of this study is to propose and test a gas challenge that is truly ''iso-metabolic,'' by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 64 publications
(119 reference statements)
1
36
1
Order By: Relevance
“…11 In addition, in our previous study 6 it was impossible to discern the metabolic impact of hypercapnia independent to the impact of severe hypoxia. As recently reported, 12 the attending hypoxia may well offset some of the reduction in CMRO 2 attributed to hypercapnia.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…11 In addition, in our previous study 6 it was impossible to discern the metabolic impact of hypercapnia independent to the impact of severe hypoxia. As recently reported, 12 the attending hypoxia may well offset some of the reduction in CMRO 2 attributed to hypercapnia.…”
Section: Introductionsupporting
confidence: 63%
“…Hypoxia may increase the CMRO 2 4,5,12 and in turn counter some of the metabolic depression from hypercapnia during apnea. Using MRI, Peng et al, 12 recently quantified the opposing facet of hypoxia and hypercapnia on the CMRO 2 in humans. Here, Peng et al reported that hypercapnia (5% CO 2 inhalation) reduced the CMRO 2 by $8%, hypoxia (13% O 2 , balanced with N 2 ) increased the CMRO 2 by $17%, but the combination of the two (5% CO 2 and 13% O 2 , balanced with N 2 ) had no effect on the CMRO 2 .…”
Section: Influence Of Hypoxia On the Cmromentioning
confidence: 99%
“…The coefficient α denotes the dependence of venous oxygenation on EtCO 2 . Previous studies have reported that value of α is between 1 and 2%/mmHg . In this study, because we measured Y v and EtCO 2 twice on each scanner, we were able to calculate the value of α from the ratio between Y v and EtCO 2 differences, which was found to be 1.6%/mmHg.…”
Section: Methodsmentioning
confidence: 82%
“…B 371: 20150353 the assumed blood flow and volume coupling between iso-metabolic stimulation and the functional stimulus/task under investigation. The identification of clinically translatable iso-metabolic perturbers remains an active area of research [70], as does the relationship between flow and volume changes under various ( patho)physiological conditions. Further insight into the metabolic changes in the peri-infarct tissue may be attained by combining BOLD fMRI with complementary MRI approaches such as amide proton transfer imaging to assess tissue pH.…”
Section: Discussionmentioning
confidence: 99%